2021
DOI: 10.3389/fphys.2020.624287
|View full text |Cite
|
Sign up to set email alerts
|

Function Analysis of P450 and GST Genes to Imidacloprid in Aphis craccivora (Koch)

Abstract: Aphis craccivora (Koch) is an economically important pest that affects legumes in worldwide. Chemical control is still the primary efficient method for A. craccivora management. However, the mechanism underlying insecticide resistance in A. craccivora has not been elucidated. A previous study observed that piperonyl butoxide (PBO) and diethyl maleate (DEM) significantly synergized imidacloprid in A. craccivora field populations, indicating that cytochrome P450 (P450) and glutathione S-transferase (GST) genes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Detoxification enzymes occur naturally in various biological processes, functioning on the target sites to neutralize various toxins prevalent in the insect body ( Lin et al, 2015 ; Bhandari et al, 2021 ; Siddiqui et al, 2022 ). According to some previous studies, the biochemical characterization of insect resistance to pesticides is connected to pesticide sensitivity at the target site and pesticide detoxification by metabolic enzymes (acetylcholinesterase, carboxylesterase, glutathione S-transferase, and cytochrome P450) ( Wu et al, 2014 ; Ismail, 2020 ; Yang et al, 2021 ; Siddiqui et al, 2022 ). These enzymes are crucial in detoxifying xenobiotics ( Hu et al, 2014 ), where their hosts can utilize these enzymes as biological indicators during pesticide detoxification ( Khan et al, 2021 )—for instance, Zhang et al (2016) reported that detoxification enzymes (cytochrome P450 genes) were detected during detoxification of fipronil in the red imported fire ants ( Solenopsis invicta Buren), where up to 36.4-fold rise in resistance was recorded following exposure of the ants to fipronil.…”
Section: Molecular Mechanisms By Which Enzymes Mediate Pesticide Deto...mentioning
confidence: 99%
“…Detoxification enzymes occur naturally in various biological processes, functioning on the target sites to neutralize various toxins prevalent in the insect body ( Lin et al, 2015 ; Bhandari et al, 2021 ; Siddiqui et al, 2022 ). According to some previous studies, the biochemical characterization of insect resistance to pesticides is connected to pesticide sensitivity at the target site and pesticide detoxification by metabolic enzymes (acetylcholinesterase, carboxylesterase, glutathione S-transferase, and cytochrome P450) ( Wu et al, 2014 ; Ismail, 2020 ; Yang et al, 2021 ; Siddiqui et al, 2022 ). These enzymes are crucial in detoxifying xenobiotics ( Hu et al, 2014 ), where their hosts can utilize these enzymes as biological indicators during pesticide detoxification ( Khan et al, 2021 )—for instance, Zhang et al (2016) reported that detoxification enzymes (cytochrome P450 genes) were detected during detoxification of fipronil in the red imported fire ants ( Solenopsis invicta Buren), where up to 36.4-fold rise in resistance was recorded following exposure of the ants to fipronil.…”
Section: Molecular Mechanisms By Which Enzymes Mediate Pesticide Deto...mentioning
confidence: 99%
“…In the insect body system, various potential natural enzymes are linked with different biological processes and play a vital role in toxic detoxifying substances in target sites ( Lin et al, 2015 ; Naik et al, 2018 ; Bhandari et al, 2021 ). Based on some previous reports, it is found that resistance or tolerance of pesticides is interlinked with these biochemical processes which are held in the insect body and sensitivity of pesticides which are further degraded by metabolic enzymes such as hydrolase, esterase, laccase, acetylcholinesterase, carboxylesterase, glutathione S-transferase, cytochrome P450 and many more ( Ismail, 2020 ; Clark et al, 2021 ; Yang Y. -X. et al, 2021 ; Ahmad et al, 2022b ; Siddiqui et al, 2022 ).…”
Section: Functions Of Insect Gut Microbiotamentioning
confidence: 99%
“…In recent years, there are a variety of detoxification enzymes encoded in insect genomes, including glutathione S-transferase (GST), cytochrome oxidase P450 (CYP), and carboxylesterase (CarE, also known as CCE/EST/CES) [ 33 , 34 ] that have potential activities in xenobiotic compounds detoxification. Furthermore, transcriptional regulation of gene expression of GST, CarE, and AchE enzymes in insects after insecticide application has been utilized for understanding the insect response and insecticidal mechanism to various xenobiotic compounds stresses [ 35 , 36 ]. However, molecular mechanisms remain unclear for the insecticidal activities of the essential oils from Ocimum basilicum , Nigella sativa, and Lavandula angustifolia medicinal plants against the stored product insect pest Sitophilus oryzae (L.).…”
Section: Introductionmentioning
confidence: 99%